U2 and the religious impulse: take me higher - Calhoun, Scott D. (Bloomsbury studies in religion and popular music, 2018)
Introduction: U2's Sacrament of Sound / Scott Calhoun -- Part 1. Meet Me in the Sound. Chapter 1. "Edge, Ring Those Bells": The Guitar and Its Spiritual Soundscapes in Early U2 / Henrik Marstal ; Chapter 2. "Looking to Fill That God-Shaped Hole": The Evolution of U2's Spiritually Evocative Musical Gestures / Christopher Endrinal ; Chapter 3. Divine Moves: Pneumatology as Passionate Participation in U2's "Mysterious Ways" / Steve Taylor -- Part 2. Lift Me Out of These Blues. Chapter 4. "Hold On To Love": U2's Bespoke Exorcism of the 1960s / Nicola Allen and Gerry Carlin ; Chapter 5. Sarajevo and the PopMart Lemon: The Fractured Form and Function of U2's Walk through the Valley of the Shadow of Death / Richard S. Briggs ; Chapter 6. "You Carried the Cross of My Shame": From Crippling Stigma to Infectious Joy in the Songs of U2 / Mark Meynell -- Part 3. Escape Yourself, And Gravity. Chapter 7. The Technological Reach for the Sublime on U2's 360° Tour / Kimi Kärki ; Chapter 8. The "Moment of Surrender": Medieval Mysticism in the Music of U2 / Brenda Gardenour Walter ; Chapter 9. "In God's Country": Spatial Sacredness in U2 / Michael R. MacLeod and Timothy Harvie -- Part 4. You Give Me Something I Can Feel. Chapter 10. "You Don't See Me But You Will": Jewish Thought and U2 / Naomi Dinnen ; Chapter 11. "Like Faith Needs a Doubt": U2 and the Theist/Nontheist Dialogue / Angela Pancella ; Chapter 12. Finding What They're Looking For: Evangelical Teen Fans and Their Desire for U2 to Be a Christian Band / Neil R. Coulter ; Chapter 13. U2 and the Art of Being Human / Mark Peters -- Notes -- References -- Index.